Damage Evaluation of Corroded Reinforced Concrete Beam Based on Acoustic Emission Signal Strength - Shahid, Khairul Anuar; Muhamad Bunnori, Norazura; Kamarudin, Mohd Khairul (International Journal of Integrated Engineering, 2025)
An acoustic emission (AE) technique has been used to monitor crack damage in different initial conditions of corroded reinforced concrete beams under a simplified cyclic load test (SCLT). Limited studies have assessed the validity of AE techniques for corroded reinforced concrete structures, especially in a full-scale specimen. This study aimed to explore damage evaluation techniques based on the AE signal strength parameter. The beam specimens were exposed to 45 days of the corrosion process, with the corrosion accelerated using the impressed current technique. The results obtained were then compared to those of the control specimen. The AE signal strength data analysis revealed that the signal strength parameter is consistent with visual observation (crack mapping) during SCLT. Additionally, the presence of corrosion in the reinforced concrete beam reduced the signal strength due to fewer cracks forming in the corroded specimen. Therefore, the AE signal strength parameter analysis seems promising for non-destructive evaluation in structural health monitoring.